Medical Waste Management: The Need For Effective Regulation of The Minister of Environment And Forestry In Indonesia - Ontran Sumantri Riyanto; Adi Purnomo; Yohana Kristiyaning Rahayu; Arif Wahyudi (International Journal of Science, Technology & Management, 2021)
Waste resulting from an activity or production is highly undesirable in human life because waste negatively impacts life, especially for human health. Hospitals are one of the institutions that produce considerable waste and can have a devastating impact on the environment. Because medical waste has the potential to cause problems for the environment as well as to human health. The most dangerous hospital waste is infectious medical waste. Experts and skilled should appropriately handle infectious waste in its management. This research is empirical legal research using a statutory, conceptual, and sociological approach. As well as conducting interviews and observations with the analysis used is qualitative descriptive analysis. It is expected that the management and management of the hospital can carry out the medical waste treatment by the regulations that have been published by the government, and the government must carry out strict supervision so that medical waste does not cause pollution to the environment.